A Python tool to determine the thickness of the hydrate layer around clinker grains using SEM-BSE images - Kleiner, Florian; Becker, Franz; Rößler, Christiane; Ludwig, Horst Michael (Journal of Microscopy, 2024)
To accurately simulate the hydration process of cementitious materials, understanding the growth rate of C-S-H layers around clinker grains is crucial. Nonetheless, the thickness of the hydrate layer shows substantial variation around individual grains, depending on their surrounding. Consequently, it is not feasible to measure hydrate layers manually in a reliable and reproducible manner. To address this challenge, a software has been developed to statistically determine the C-S-H thickness, requiring minimal manual interventions for thresholding and for setting limits like particle size or circularity. This study presents a tool, which automatically identifies suitable clinker grains and and perform statistical measurements of their hydrate layer up to a specimen age of 28 days. The findings reveal a significant increase in the C-S-H layer, starting from 0.45 (Formula presented.) after 1 day and reaching 3.04 (Formula presented.) after 28 days. However, for older specimens, the measurement of the C-S-H layer was not feasible due to limited pore space and clinker grains.
CRIS-Team Scopus Importer:2024-03-15
Keywords: calcium silicate hydrate; hydrate layer; hydration

C-S-H Pore Size Characterization Via a Combined Nuclear Magnetic Resonance (NMR)-Scanning Electron Microscopy (SEM) Surface Relaxivity Calibration - Naber, Christoph; Kleiner, Florian; Becker, Franz; Long Nguyen-Tuan; Roessler, Christiane; Etzold, Merlin A.; Neubauer, Jürgen (Materials, 2020)
A new method for the nuclear magnetic resonance (NMR) surface relaxivity calibration in hydrated cement samples is proposed. This method relies on a combined analysis of 28-d hydrated tricalcium silicate samples by scanning electron microscopy (SEM) image analysis and H-1-time-domain (TD)-NMR relaxometry. Pore surface and volume data for interhydrate pores are obtained from high resolution SEM images on surfaces obtained by argon broad ion beam sectioning. These data are combined with T-2 relaxation times from H-1-TD-NMR to calculate the systems surface relaxivity according to the fast exchange model of relaxation. This new method is compared to an alternative method that employs sequential drying to calibrate the systems surface relaxivity.
CRIS-Team WoS Importer:2020-05-22

Enhanced alite dissolution by CAH10 addition - Becker, Franz; Götz-Neunhoeffer, Friedlinde; Neubauer, Jürgen (Cement and Concrete Research, 2023)
The influence of varying Al addition in the form of CAH10 on the hydration of alite was studied to gain further insights into the alite hydration mechanisms in the presence of increased Al concentration in pore solution. Therefore, pure alite and mixtures of alite and CAH10 were investigated by means of isothermal heat flow calorimetry, XRD and pore solution chemistry analysis. The two occurring hydration events can be attributed to the precipitation of two different silicate-bearing hydrate phases, C2ASH8 and C-(A)-S-H. In this case, the consumption and removal of Al in pore solution initiated the change to C-(A)-S-H-forming hydration. Furthermore, the formation of C2ASH8 and the alite reaction rate and reaction were directly influenced by the amount of Al provided by CAH10 addition, leading to an alite reaction turnover of up to 68–86 % within 48 h.
CRIS-Team Scopus Importer:2023-01-06
Keywords: Ca3SiO5 (D); Hydration (A); Hydration products (B); Pore solution (B); X-ray diffraction